Effectivity of heat shocking methods on the physical and microbial characteristics of green mussels (Perna viridis) - Manalo, Marilen Salvador; Azanza, Ma. Patricia V. (2003)
ABSTRACT Green mussels were subjected to heat shocking treatments using steam, dry heat and boiling water. The shortest times utilized to effect 100% gaping of the shellshocks using the test treatments were determined. It was established that at 100°C, dry heat and steaming effected 100% gaping of mussels for 3 min while the same result was obtained using boiling water within 20 sec only. Other physical and microbial characteristics of shocked green mussels were also used to evaluate the efficacies of the test heat shocking treatments. Evaluation of percentage weight loss and gape opening effected the highest % meat yield at 36.7%. Dry heated and steamed samples gave percentage meat yield of 33.6% and 30.2%, respectively. Statistical analysis at 5% level of significance showed that there was no significant difference among heat shocked samples evaluated for pH, Aw and % drip weight. Aside from opening the shell, the heat shocking modes effectively caused count reductions of TPC, coliform and VIbrio spp. Microbial evaluation of treated mussels showed concentrations ranging from 10^1 - 10^3 CFU/g, ≤10^3 MPN/g and ≤10^1 CFU/g for TPC, coliform and Vibrio spp. counts, respectively. The E. coli counts were <3.00 MPN/g for both the untreated and heat shocked green mussels. Results of the polyvalent somatic (0) test confirmed the absence of Salmonella spp. per 25g of tested samples. It was recommended that in order to get the quality profile of heat shocked green mussels, sensory analysis should be done simultaneously with physical and microbial evaluations of the mussel samples. Cost analysis of each heat shocking procedure should also be included in future studies for the benefit of the sector of mussel industry, aiming to adapt the heat shocking technology.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mussels; Mussels -- Microbiology